The Santa suit - Andrews, Mary Kay, 1954- (New York, NY : St. Martin's Press, an imprint of St. Martin's Publishing Group, 2021)
"The newly-divorced Ivy Perkins buys an old farmhouse sight unseen, she is definitely looking for a change in her life. . . At the top of a closet, Ivy finds an old Santa suit [and] in the pocket of she finds a note written in a childish hand: it's from a little girl who has one Christmas wish, and that is for her father to return home from the war. This discovery sets Ivy off on a mission. Who wrote the note? Did the man ever come home?"--
"A novel"-- Jacket.
Keywords: Divorced women -- Fiction; Moving, Household -- Fiction; Man-woman relationships -- Fiction; Family secrets -- Fiction; Letters -- Fiction; Small cities -- Fiction; Community life -- Fiction; Christmas fiction; Novellas